Measuring Asymmetric Ionic Current Waveform Through Micropores for Detecting Reduced Red Blood Cell Deformability Due to Plasmodium falciparum Infection - Kazumichi Yokota; Ken Hirano; Kazuaki Kajimoto; Muneaki Hashimoto (Sensors)
The mechanisms underlying reduced deformability of red blood cells (RBCs) in Plasmodium falciparum remain unclear. The decrease in RBC deformability associated with malarial infection was measured using ektacytometry, and only mean values were evaluated. In this study, we report the development of a microfluidic sensing device that can evaluate decreased RBC deformability at the single-cell level by measuring ionic current waveforms through micropores. Using an in vitro culture system, we found that when RBC deformability was reduced by P. falciparum infection, ionic current waveforms changed. As RBC deformability decreased, waveforms became asymmetric. Computer simulations suggested that these waveform parameters are largely independent of RBC size and may represent a reliable indicator of diminished deformability. This novel microfluidic RBC deformability sensor allows for detailed single-cell analysis of malaria-associated deformability reduction, potentially aiding in elucidating its pathology.